Ginger (Zanjabil) in the Perspective of Classical Interpretation, Modern Interpretation, and Herbal Medicine - Atabik, Ahmad (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2023)
This research examines the scientific miracles of ginger (zanjabil) in the Qur'an combined with the interpretation of classical scholars about ginger in Qs. Al-Insan: 17-18. The method used in this study uses library research based on data from classic commentary books, scientific interpretations, and various research journals on ginger. The finding of this paper is that ginger in the treasures of classical interpretation is a dish for the inhabitants of heaven mixed with salsabil spring water so that it becomes a ginger drink. The interpretation of classical interpreters is normative based on linguistic aspects and the text's literal meaning. While modern interpreters scientifically interpret ginger as a highly nutritious food and beverage ingredient because it contains shogaol, gingerol, zingiberene, and zingerone. Therefore ginger can be used as herbal medicine to cure various internal diseases. Several scientific research findings suggest that ginger can treat pain, inflammation, and digestive disorders, relieve nausea and vomiting, boost immunity, maintain heart health, and improve brain function. The contribution of this paper shows that strengthening scientific argumentation against an object mentioned by the Qur'an has unique features. Jahe (Zanjabil) dalam Perspektif Tafsir Klasik, Tafsir Modern, dan Pengobatan Herbal. Penelitian ini mengkaji tentang mukjizat ilmiah jahe (zanjabil) dalam al-Qur’an yang dipadukan dengan penafsirkan ulama klasik tentang jahe dalam Qs. al-Insan: 17-18. Metode yang ditempuh dalam penelitian ini menggunakan liberary research berdasarkan data-data dari kitab tafsir klasik, tafsir ilmi dan pelbagi jurnal penelitian tentang jahe. Temuan tulisan ini adalah jahe dalam khazanah tafsir klasik merupakan hidangan bagi penduduk surga dengan dicampur mata air salsabilsehingga menjadi minuman jahe. Penafsiran penafsir klasik terbilang normatif didasarkan pada aspek linguistikdan makna literal teks. Sementara penafsir modern secara saintifik menafsirkan jahe sebagai bahan makanan dan minuman yang berkhasiat tinggi karena mengandung shogaol, gingerol, zingiberen dan zingeron. Sebab itu jahe bisa dijadikan sebagai obat herbal untuk menyembuhkan pelbagai penyakit dalam. Beberapa temuan penelitian sains menyebut jahe dapat digunakan untuk mengobati rasa sakit dan peradangan, gangguan pencernaan, meredakan mual dan muntah, meningkatkan kekebalan tubuh, menjaga kesehatan jantung, serta meningkatkan fungsi otak. Kontribusi tulisan ini menunjukkan penguatan argumentasi saintifik terhadap suatu benda yang disebut oleh al-Qur’an memang memiliki keistimewaan.